Implementasi Kebijakan Sistem Pelaporan Terintegrasi Aplikasi Software Pada Bidang Sumber Daya Aparatur Pada Satuan Polisi Pamong Praja Provinsi Sumatera Utara - Muhammad Faiys Nasution; Zainuddin Zainuddin; Budi Hartono (Mahesa Research Center, 2022)
This study aims to find out and analyze: Implementation of an integrated reporting system software application in the field of apparatus resources in the civil service police unit of North Sumatra Province and what factors are the obstacles in implementing an integrated reporting system software application in the field of apparatus resources in the police unit. civil service of North Sumatra Province. The method used is descriptive qualitative with a phenomenological approach to Employee Performance Improvement at the Regional Personnel Board of North Sumatra Province. Thus the researcher becomes the interpreter of the interview findings, documentation and also observations during the process. The results of the study stated that Communication in the Civil Service Police Unit of North Sumatra Province needs to be intensively improved so that the Integrated Reporting System Application Software can provide optimal results by monitoring activities in the Regency / City on a regular basis in order to understand and know the existing programs. in the Civil Service Police Unit located in the Regency / City. The disposition or attitude of policy implementers should know what to do and be able to implement it so that in practice there is no bias or ambiguity. Resources are one of the supporting factors in policy implementation, therefore in order to achieve policy implementation it is necessary to provide adequate resources in order to support the policy implementation process.